Aetiology of Bacteraemia as a Risk Factor for Septic Shock at the Onset of Febrile Neutropaenia in Adult Cancer Patients - Rosa, Regis Goulart (Hindawi Publishing Corporation, 2014)
Septic shock (SS) at the onset of febrile neutropaenia (FN) is an emergency situation that is associated with high morbidity and mortality. The impact of the specific aetiology of bloodstream infections (BSIs) in the development of SS at the time of FN is not well established. The aim of this study was to evaluate the association between the aetiology of BSIs and SS at the time of FN in hospitalised adult cancer patients. This prospective cohort study was performed at a single tertiary hospital from October 2009 to August 2011. All adult cancer patients admitted consecutively to the haematology ward with FN were evaluated. A stepwise logistic regression was conducted to verify the association between the microbiological characteristics of BSIs and SS at the onset of FN. In total, 307 cases of FN in adult cancer patients were evaluated. There were 115 cases with documented BSI. A multivariate analysis showed that polymicrobial bacteraemia (P = 0.01) was associated with SS. The specific blood isolates independently associated with SS were viridans streptococci (P = 0.02) and Escherichia coli (P = 0.01). Neutropaenic cancer patients with polymicrobial bacteraemia or BSI by viridans streptococci or Escherichia coli are at increased risk for SS at the time of FN.